Exposure to Di-2-ethylhexyl Phthalate and Benign Prostatic Hyperplasia, NHANES 2001-2008 - Yang, Luchen; Liu, Zhenghuan; Peng, Zhufeng; Song, Pan; Zhou, Jing; Wang, Linchun; Chen, Junhao; Dong, Qiang (Frontiers in Endocrinology, 2022)
30 % of men suffer from benign prostatic hyperplasia (BPH) in worldwide, previous study suggested ubiquitous Di-(2-ethylhexyl) phthalate (DEHP) exposure is associated male disorders. The objective of this study was to study the potential association by the 2001–2008 National Health and Nutrition Examination Survey (NHANES) data. The data was collected, and multiple logistic regression was adapted to measure the association. The concentrations of DEHP (∑DEHP) were calculated by each metabolite and split into quartiles for analysis. Results showed that the OR decreased with increased ∑DEHP concentration. In the crude model, the odds ratio (OR) for the second quartile (OR = 1.60, 95 %CI [1.24, 2.07]) was obviously higher compared with the lowest quartile. However, the odds ratio (OR) for the highest quartile (OR = 0.55, 95 %CI [0.44,0.69]) lower than that for the third quartile (OR = 0.77, 95 %CI [0.61, 0.97]), and the OR for the third and highest quartile was significantly lower than that of the lowest quartile, which suggested biphasic effects of DEHP based on concentration. The results showed the same trend after adjusting for confounding factors. This study adds limited evidence to study this topic, and further research is needed to determine if the status of BPH can be changed by controlling DEHP exposure.